Metolazone Add-On Therapy in Heart Failure: A Cohort Study from Persian Registry of Cardiovascular Disease/Heart Failure (PROVE/HF) - Farzad Rahimi; Mehrbod Vakhshoori; Maryam Heidarpour; Fatemeh Nouri; Kiyan Heshmat-Ghahdarijani; Mohammad Fakhrolmobasheri; Davood Shafie (Critical Care Research and Practice)
Background. One of the strategies for overcoming diuretic resistance among heart failure (HF) patients is adding thiazide-type diuretics. The main aim of this article is to compare the adverse clinical outcomes, including death and re-hospitalization, among individuals suffering from severe acute decompensated HF (ADHF) that consumed furosemide or furosemide plus metolazone. Methods. This retrospective cohort study was done in the context of the Persian registry of cardiovascular disease (PROVE) from September 2017 to September 2018. One thousand and four hundred thirty-eight individuals (furosemide: 972 and furosemide plus metolazone: 466) with the final diagnosis of severe ADHF (left ventricular ejection fraction < 30%) were selected and followed for 10.3 ± 7.8 months. The association between two groups, as mentioned above, with the incidence of death and re-admission, was evaluated with different models. Results. The mean age of the study population was 68.19 ± 12.98 years. There was no significant relation in terms of death or re-hospitalization between patients with different diuretic regimens. After adjustment of potential confounders, we found that adding metolazone as an adjuvant HF therapy was not independently associated with death or re-hospitalization (hazard ratio (HR): 0.78,95% confidence interval (CI) = 0.59–1.03, P = 0.085, and odds ratio (OR): 0.80, 95% CI: 0.60–1.07, P = 0.135, respectively). Conclusion. Our findings revealed that adding metolazone in patients with furosemide resistance is not associated with higher morbidity and mortality. Therefore, usage of these two therapeutic agents could be a helpful strategy for severe HF patients.